Portugal 1974-2010: da Revolução dos Cravos ao bouquet do casamento - Fernando Cascais (Mélanges de la Casa de Velázquez, 2020)
Homosexuality was punishable in Portugal under the 1852 Penal Code and by the 1912 law, until it was depenalized in the 1982 Penal Code, in the aftermath of the 25th of April 1974 Revolution that overthrew the fascist regime of Estado Novo. Prior to 1974, the existence of any LGBT movement would have been completely impossible and it was not until the mid-1990s, and only after a few ephemeral attempts, that it finally settled for good. Its sociogenesis was determined by the accession to the European Union, by the change in the revolutionary political culture that rendered the partisan forces of the Left welcoming to the LGBT agendas, and by the struggle against the AIDS epidemic, out of which non-governmental organisations the first LGBT associations formed. Finally, the process that led to the implementation of a same-sex marriage law confirms the «velvet triangle» thesis that was applied beforehand to identical processes at the international level.